Digital Media vs Traditional Promotion: The Changing Dynamics of Silk Road Tourism Marketing in Uzbekistan - Fayzullayeva Gulchexra (Review of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study examines the factors influencing tourism promotion effectiveness in Uzbekistan, focusing on the impact of digital and traditional media channels on tourists’ travel behavior and decision-making toward Silk Road destinations. Research Methodology: A quantitative approach was employed, using primary data collected through structured online questionnaires from 44 respondents. Data were analyzed using SPSS, including linear regression for relationships between heritage-related factors and tourism behavior, and descriptive analysis of promotional influences. Results: Digital media, particularly social media platforms such as Instagram, YouTube, and TikTok, were found to be significantly more effective than traditional channels in influencing travel decisions. Social media accounted for the strongest influence on tourist behavior (45.5%), whereas traditional channels like television and travel agencies showed minimal impact. Besides promotional media, accessibility and heritage site preservation were also statistically significant factors affecting travel decisions (p = 0.025; p = 0.004). Conclusions: The findings indicate a clear shift from centralized or traditional tourism marketing toward digitally-driven platforms, where interactive, user-generated content enhances destination image and engagement. While infrastructure and heritage protection remain important, optimizing digital marketing strategies is crucial for improving global competitiveness and tourist engagement with Uzbekistan’s Silk Road destinations. Limitations: The study’s sample size was relatively small, with only 44 respondents, potentially limiting generalizability. Additionally, the research focused solely on Uzbekistan, which may not fully reflect tourism promotion dynamics in other Silk Road countries. Contribution: This study provides new quantitative insights into the effectiveness of digital versus traditional promotional channels for heritage tourism in Uzbekistan, offering practical guidance for policymakers and tourism stakeholders to enhance destination marketing strategies.